Previous treatment with anthracycline does not affect the course of sepsis in cancer patients: Retrospective cohort study - Camille Windsor; Adrien Joseph; Stephanie Pons; Djamel Mokart; Frederic Pène; Achille Kouatchet; Alexandre Demoule; Fabrice Bruneel; Martine Nyunga; Edith Borcoman; Matthieu Legrand; Michael Darmon; et al. (Journal of Intensive Medicine)
Background: Cancer patients who are exposed to sepsis and had previous chemotherapy may have increased severity. Among chemotherapeutic agents, anthracyclines have been associated with cardiac toxicity. Like other chemotherapeutic agents, they may cause endothelial toxicity. The aim of this study was to evaluate the effect of anthracycline treatment on the outcome of cancer patients with sepsis. Methods: Data from cancer patients admitted to intensive care units (ICUs) for sepsis or septic shock were extracted from the Groupe de Recherche Respiratoire en Réanimation Onco-Hématologique database (1994–2015). Comparison between patients who received anthracycline and those who did not was performed using a propensity score, including confounding variables (age and underlying diseases). A competing risk adjusted for severity of illness (Sequential Organ Failure Assessment [SOFA] score) was used to analyze the duration of vasopressor requirement. Results: Among 2046 patients, 1070 (52.3%) patients who received anthracycline were compared with 976 (47.7%) who did not. The underlying disease was mostly acute hematological malignancy (49.2%). Sepsis, mostly pneumonia (47.7%), had developed 2 days (interquartile range [IQR]:1–4 days) prior to ICU admission. Most patients (n=1156/1980,58.4%) required vasopressors for 3 days (IQR: 2–6 days). Factors associated with the need for vasopressors were aplasia (hazard ratio [HR]=1.72, 95% confidence interval [CI]: 1.21 to 2.47, P=0.002) and day 1 respiratory SOFA score (HR=7.07, 95% CI: 2.75 to 22.1, P <0.001). Previous anthracycline treatment was not associated with an increased risk of vasopressor use. The duration of vasopressors was not different between patients who received anthracycline and those who did not (P=0.79). Anthracycline was not associated with ICU mortality. Conclusion: Previous anthracycline treatment did not alter the course of sepsis in a cohort of cancer patients admitted to intensive care with sepsis.